Nucleophilicities and Nucleofugalities of Thio‐ and Selenoethers. Issue 44 (30th June 2021) - Maji, Biplab; Duan, Xin‐Hua; Jüstel, Patrick M.; Byrne, Peter A.; Ofial, Armin R.; Mayr, Herbert
Abstract: Rate constants for the reactions of dialkyl chalcogenides with laser flash photolytically generated benzhydrylium ions have been measured photometrically to integrate them into the comprehensive benzhydrylium‐based nucleophilicity scale. Combining these rate constants with the previously reported equilibrium constants for the same reactions provided the corresponding Marcus intrinsic barriers and made it possible to quantify the leaving group abilities (nucleofugalities) of dialkyl sulfides and dimethyl selenide. Due to the low intrinsic barriers, dialkyl chalcogenides are fairly strong nucleophiles (comparable to pyridine and N ‐methylimidazole) as well as good nucleofuges; this makes them useful group‐transfer reagents. Abstract : Strong nucleophiles and weak Lewis bases : Kinetic studies by laser flash photolytic methods reveal that dialkyl sulfides and selenides are strong nucleophiles, comparable to pyridine and N ‐methylimidazole. Because of their low Lewis basicity (6 to 7 orders of magnitude lower than that of pyridine with respect to C‐centred Lewis acids) they are also good nucleofuges, which makes them useful group‐transfer reagents. Low Marcus intrinsic barriers account for the different ranking of dialkyl chalcogenides in nucleophilicity and Lewis basicity scales.